1990
DOI: 10.1159/000119451
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Connections between Platelet Monoamine Oxidase Activity and Behavior: Relationships with Performance in Neuropsychological Tasks

Abstract: Platelet MAO activity has been found to have behavioral (psychiatric and personality) correlates. The purpose of the present study was to explore the nature of the connections between platelet MAO activity and behavior by analyzing performance in neuropsychological tasks in relation to platelet MAO activity, measured in 37 male subjects. The following neuropsychological tests were given: a finger tapping and alternation test, a reaction time test, a perceptual maze test, a perspective fluctuation task (the Nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…In healthy adults, a low MAO activity is associated with activation of the right cerebral hemisphere and frontal activity, which leads to motor disinhibition. In psychomotor tests, in- dividuals with low MAO activity manifest a preference for speed over precision (10). These observations support our hypothesis that monoamine metabolites measured at birth could be in part genetically predetermined by enzymatic activity, and therefore associated with subsequent manual performance of the child.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In healthy adults, a low MAO activity is associated with activation of the right cerebral hemisphere and frontal activity, which leads to motor disinhibition. In psychomotor tests, in- dividuals with low MAO activity manifest a preference for speed over precision (10). These observations support our hypothesis that monoamine metabolites measured at birth could be in part genetically predetermined by enzymatic activity, and therefore associated with subsequent manual performance of the child.…”
Section: Discussionsupporting
confidence: 80%
“…Oxidation of dopamine is a known source of free radicals that are particularly harmful to membranes (9). A study showed that the activity of MAO is in part genetically predetermined and that its high activity can be associated, in normal subjects, with right hemisphere activity and a motor disinhibition (10). Additionally, numerous animal studies illustrated the adverse effects of maternal psychological stress and prenatal chemical exposures on functioning of the monoaminergic system and on postnatal behavior (1).…”
mentioning
confidence: 99%
“…The outcome of this study showed that several personality traits were significantly associated with AP-2␤ genotype. The observed frequencies of genotypes in our sample were [CAAA] 5 13.9%. In the present sample, simple regression analyses did not reveal any significant correMolecular Psychiatry lation between age or gender of the subjects and any of the personality traits that were estimated by the KSP.…”
Section: Transcription Factor Ap-2␤ and Personalitymentioning
confidence: 78%
“…Also investigations on the correlation between trbc MAO activity and neuropsychological measures support the notion of trbc MAO as a stable biological marker, where the simplest way to describe the results is to say that low MAO probands prefer speed before accuracy. 13 It is crucial to notice that drug-induced inhibition of trbc MAO does not result in major alterations in temperament and knock-out mice deficient in MAO-B do not display changed behavior.…”
Section: Thrombocyte Monoamine Oxidase As a Biological Markermentioning
confidence: 99%
“…Some documents indicate a close relations in hippocampus between dopaminergic functions of reward related-associative learning (Di Chiara, 1999), reward prediction and incentive salience (Berridge & Robinson, 1998;Schultz 1998;Everitt et al, 1999), and serotonergic functions of disinhibition and impulsivity (Linnoila et al, 1983;Af Klinteberg et al, 1990;Winstanley et al, 2004) because of numerous specific interactions between the two systems.…”
Section: Todaymentioning
confidence: 99%